Preparing African American Males for College: A Group Counseling Approach. Issue 2 (2nd April 2020) - Hines, Erik M.; Hines, Mia R.; Moore, James L.; Steen, Sam; Singleton, Paul; Cintron, Dakota; Golden, Monique N.; Traverso, Kimberly; Wathen, Bobbi-Jo; Henderson, Jerrod
ABSTRACT: In this article, the authors discuss how to prepare African American males for college through group counseling. The authors created, Achieving Excellence: A College Readiness Curriculum for African Males, a five-session, 50 minute group curriculum for sophomores to facilitate the process of college planning. The Eight Components of College and Career Readiness was used as a framework to guide the curriculum. Implications for school counselors are included in this article.